Kehamilan Kembar Disertai Mola Hidatidosa - Harya Narottama; Erry Gumilar; Brahmana Askandar (Jurnal Ilmiah Kedokteran Wijaya Kusuma, 2019)
Twin pregnancy with Hydatidiform Mole is a rare case, only about 1 in 22.000 to 100.000 pregnancies. Molar pregnancy with triplet pregnancy is even rarer, which is only 6 cases reported and mostly occurred in women who received therapy for infertility. Management in cases of twin pregnancy with hydatidiform mole is dilemmatic both for the patient and physician. We present a case of 29 years old woman with her first pregnancy of twin fetuses complicated with hydatidiform mole. Diagnostic approaches were made mainly by ultrasound examination, continued with laboratory and radiology examinations which some did not performed due to worsened vaginal bleeding. This case ended with premature labor with the result of delivery of two babies and placenta with vesicles which is a characteristic of hydatidiform mole.